The Effectiveness of Constructed Wetlands in Managing Coal Mining Wastewater - Abdullah, Deden Disa; Hamdan, Alifal (CV. Publikasi Indonesia, 2024)
Mining activities, especially coal mining, produce wastewater containing heavy metals such as manganese and iron, which can degrade water quality and harm ecosystems. Effective wastewater management is crucial to meet environmental quality standards and reduce ecological risks. This research aims to evaluate the effectiveness of constructed wetlands in treating coal mine wastewater by assessing critical water quality parameters such as pH, Suspended Solids (TSS), Total Iron (Fe), and Total Manganese (Mn). The research uses a descriptive method involving field sampling and laboratory analysis. Water samples were collected from settling pond BB-18 PPA-BA, both before and after the installation of constructed wetlands. The parameters tested include pH, TSS, Total Iron, and Total Manganese, following standard environmental testing protocols. The implementation of constructed wetlands significantly improved water quality. The measured values after treatment were pH 6.90, TSS 18.20 mg/L, Total Iron 0.31 mg/L, and Total Manganese 2.75 mg/L, all within permissible environmental quality standards. Constructed wetlands effectively reduce pollutants in coal mine wastewater, enabling compliance with environmental quality standards. This approach combines active and passive treatment methods, providing a sustainable and cost-effective wastewater management solution for coal mining operations.